Effects of Gamma Irradiation on Phenotypic Changes in Vanda Hybrid - Sri Hartati; Prasetyo Prasetyo; Endang Setia Muliawati (Journal of Biodiversity and Biotechnology, 2021)
Vanda Orchid is one of the most popular ornamental plants. Orchids have slow growth. One way to overcome this weakness is by using gamma-ray irradiation. This research aimed to study the morphological characters of various radiation doses resulting from the crossing of the Vanda Orchid. This study was carried out by observing the characters of vegetative growth for each plant on 0 Gy, 10 Gy, 20 Gy, 30 Gy, 40 Gy, and 50 Gy doses of gamma irradiation treatments. The observed variables were the increase in plant height, leaf length, root length, number of roots, number of leaves, leaf width, and leaf color. The results showed that the dose of gamma-ray irradiation were able to increase plant height. 10 Gy and 20 Gy, gamma-ray irradiation doses, resulted in discolored yellowing of orchid leaves. The discoloration of orchid leaves to light green occurs at irradiation doses of 30 Gy, 40 Gy, and 50 Gy. The morphological characteristics of Vanda sp. hybrid results gamma irradiation are high at dose 10-40 Gy. Keywords: characteristics; morphological; orchid.